The Relationship of Democratic Leadership Style and Conflict Management with the Performance of Public Elementary School Principals in Bekasi Regency - Wagi Ramadhan; Baharuddin; Haryono, Pauzan (Proceeding International Conference on Education, 2023)
The purpose of this study is to ascertain how the performance of public elementary school principals in Bekasi Regency is related to democratic leadership style and conflict management. This study uses correlational methodology and is quantitative. Researchers employed observation, questionnaires, interviews, and Correllation analysis to examine the data they collected. According to the study's findings, there is a relationship between democratic leadership style and school principal performance, with significance values of 0.001<0.05; there is also a relationship between conflict management and the principal's performance, with a significance value of 0.017<0.05; and there is a relationship between democratic leadership style and conflict management combined with the principal's performance, with significance values of 0.001<0.05. In summary, this study demonstrates that democratic leadership style and conflict management significantly affect school principal performance. The finding of this study suggests that in order to increase leadership efficiency and educational quality in schools, principals must develop abilities in democratic leadership and dispute resolution.